The use of ionic liquids as additive to stabilize surfactant foam for mobility control application - Hanamertani, A.S. (Elsevier B.V., 2018)
Foam application has been introduced in enhanced oil recovery processes for mobility control to overcome some issues occurred during gas injection. The stability of foam has become the main concern as it dictates the effectiveness of foam mobility control. Many attempts at enhancing foam stability under reservoir conditions involve the application of chemical additives which can produce synergistic effect in combination with surfactant. Ionic liquids (ILs), salts melting below 100 Â°C, are considered to be able to alter surface behavior of surfactant molecules, hence supporting the surfactant performance at the interface. Their alteration is expected to be favorable in improving surface properties of foam. This research has introduced ionic liquid based additives for the first time to improve surfactant foam stability. Identification of the effect of ILs was performed by conducting bulk foam experiments at ambient conditions and also at high temperature using Foamscan. The foaming properties of in-house surfactant (MFOMAX) were evaluated in the absence and presence of ILs at different mixture ratios. The results show that imidazolium- and eutectic-based ILs were able to improve surfactant foam stability to different extent at high temperature and their effect on foam stabilization was more pronounced at surfactant/IL mixture ratio of 60:40. The highest foam stability increment exhibited by the best formulation reached 136 of that achieved by the formulation without IL. This study has indicated that ionic liquid has a promising potential for improving surfactant-stabilized foam mobility control during EOR processes. Â© 2018 Elsevier B.V.